2003
DOI: 10.1002/mus.10446
|View full text |Cite
|
Sign up to set email alerts
|

Inferior mechanical properties of spastic muscle bundles due to hypertrophic but compromised extracellular matrix material

Abstract: The passive mechanical properties of small muscle fiber bundles obtained from surgical patients with spasticity (n = 9) and patients without neuromuscular disorders (n = 21) were measured in order to determine the relative influence of intracellular and extracellular components. For both types of patient, tangent modulus was significantly greater in bundles compared to identical tests performed on isolated single cells (P < 0.05). However, the relative difference between bundles and single cells was much great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
217
5
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(241 citation statements)
references
References 30 publications
8
217
5
11
Order By: Relevance
“…From a biomechanical and structural standpoint, multifidus fibers are similar to other muscle fibers in terms of slack sarcomere lengths, elastic modulus, and whether fibers express the fast or slow myosin heavy chain isoform 6,36 . Compared with upper extremity muscles 41 and more recent data on the quadriceps muscle 36 , the multifidus yields slack sarcomere lengths of about 2.2 mm and elastic moduli of about 35 kPa. This indicates that the fibers themselves have biomechanical properties comparable with those of other muscles in the body.…”
Section: Discussionmentioning
confidence: 77%
“…From a biomechanical and structural standpoint, multifidus fibers are similar to other muscle fibers in terms of slack sarcomere lengths, elastic modulus, and whether fibers express the fast or slow myosin heavy chain isoform 6,36 . Compared with upper extremity muscles 41 and more recent data on the quadriceps muscle 36 , the multifidus yields slack sarcomere lengths of about 2.2 mm and elastic moduli of about 35 kPa. This indicates that the fibers themselves have biomechanical properties comparable with those of other muscles in the body.…”
Section: Discussionmentioning
confidence: 77%
“…Spastic muscles (e.g., Tardieu et al 1982;Sinkjaer and Magnussen 1994) and isolated single muscle fiber segments were reported to be stiffer than normal. In contrast, Lieber et al (2003) showed for passive bundles muscle fibers that despite being hypertropic the collagen reinforced extracellular matrix of spastic muscle tissue was less stiff. Conceivably, if the intramuscular connective tissues are stiffer than presently modeled, more resistance to sarcomere shortening is expected.…”
Section: Limitations and Implications Of The Present Studymentioning
confidence: 90%
“…35 Spasticity is often blamed for poor hand function in patients with minimal wrist and finger extension but some preservation of flexion. Contracture and change in the morphologic features of muscle 36 contribute to a flexed posture, but poor motor control with weakness, not hypertonia, is the primary cause of disability. 37 In a randomized trial, the injection of botulinum toxin into the muscles of the arm reduced excessive flexion and the associated pain, spasms, or postures that interfered with patients' self-care, 38 but the induced muscle weakness usually does not improve the functional use of the hand.…”
Section: Targeted Therapymentioning
confidence: 99%